2014
DOI: 10.1590/s0100-06832014000100026
|View full text |Cite
|
Sign up to set email alerts
|

Soybean root growth and crop yield in reponse to liming at the beginning of a no-tillage system

Abstract: Analyzing the soil near crop roots may reveal limitations to growth and yield even in a no-tillage system. The purpose of the present study was to relate the chemical and physical properties of soil under a no-tillage system to soybean root growth and plant yield after five years of use of different types of limestone and forms of application. A clayey Oxisol received application of dolomitic and calcitic limestones and their 1:1 combination in two forms: surface application, maintained on the soil surface; an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 14 publications
0
32
0
2
Order By: Relevance
“…Phosphorus accumulation in the upper soil layers is desirable, for being the region of concentrated thinner crop roots responsible for most of the nutrient and water uptake (Bortoluzzi et al, 2014), which is reflected in a greater quantity of P accumulated in the shoots and in DM production (Chantigny et al, 2008), as observed in oat and maize (Table 3). But on the other hand, part of the P accumulated in the upper soil layers can be transferred in soluble form in the runoff solution or adsorbed to particles, to surface waters adjacent to the cultivated area, increasing the risk of water eutrophication, which is undesirable (Ceretta et al, 2010b;Wang et al, 2013;Schmitt et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorus accumulation in the upper soil layers is desirable, for being the region of concentrated thinner crop roots responsible for most of the nutrient and water uptake (Bortoluzzi et al, 2014), which is reflected in a greater quantity of P accumulated in the shoots and in DM production (Chantigny et al, 2008), as observed in oat and maize (Table 3). But on the other hand, part of the P accumulated in the upper soil layers can be transferred in soluble form in the runoff solution or adsorbed to particles, to surface waters adjacent to the cultivated area, increasing the risk of water eutrophication, which is undesirable (Ceretta et al, 2010b;Wang et al, 2013;Schmitt et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Deeper root distribution in the soil profile was evaluated by changing the soil root growth factor in the model, based on two concepts: that a better soil management and genetic modification can improve root growth at depth and increase the water available to the crop, mainly in the layer between 30 and 70 cm (FRANCHINI et al, 2009;BORTOLUZZI et al, 2014). Soil root growth factor determines the potential ability of roots to grow in respective soil layers, altering the shape of root distribution and the potential amount of water that can be extracted by the roots from the soil (MA et al, 2009).…”
Section: Deeper Root Depthmentioning
confidence: 99%
“…The first step to mitigate yield losses is to identify soybean breeding lines with advantageous traits that can help the crop to adapt to adverse conditions, such as water deficit (LEHMANN et al, 2013). Cultivars characteristics, such as deeper and denser root system (BORTOLUZZI et al, 2014), soil water conservation , nitrogen fixation drought tolerance (SINCLAIR et al, 2007), and less sensitivity of grain filling acceleration under drought (SPECHT et al, 1986) have potential to be used to develop new cultivars, more resilience to water deficit.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assim, quanto mais fino o corretivo, mais rápida será sua reação, desde que o solo esteja úmido (Alcarde et al, 1989;Tedesco e Gianello, 2000;Gonçalves et al, 2011 O sistema plantio direto (SPD) tem se destacado como uma das estratégias mais eficazes para melhorar a sustentabilidade da agricultura em regiões tropicais e subtropicais, contribuindo para minimizar perdas de solo e nutrientes por erosão. No estabelecimento do SPD, a correção da acidez do solo deve ser feita por meio de incorporação de calcário na camada arável (Costa e Rosolem, 2007;Bortoluzzi et al, 2014). Depois do sistema já estabelecido, a correção da acidez do solo é realizada por meio da aplicação de calcário na superfície, sem incorporação.…”
Section: Introductionunclassified